Bioremediation of herbicide diquat dibromide from aqueous solution with white rot fungus Phanerochaete chrysosporium - Yildirim, Numan; Ciftci, Emine; Erguven, Gokhan Onder; Durmus, Barbaros (Elsevier Science Inc, 2023)
In this study, the fungal bioremediation of herbicide diquat dibromide (DD) by white rot fungus Phanerochaete chrysosporium was studied. After bioremediation, the reduction in toxicity of the remediated media was evaluated by Daphnia magna as a model organism. For bioremediation studies, flask-level batch experiments were performed at different DD concentrations (10, 20 and 50 ppm) under static and agitated conditions. The highest reduction rates of chemical oxygen demand and total organic carbon were determined as 85.92 (for 20 ppm DD) and 87.46% (for 10 ppm DD), respectively under agitated conditions. After bioremediation, D. magna bioassay was used for toxicity assessment during 24, 48 and 72-h periods. In current study, it was observed that P. chrysosporium has very effective bioremediation capacity for diquat dibromide. The D. magna bioassay revealed that P. chrysosporium provides effective reduction in toxicity of diquat dibromide.
Keywords: Phanerochaete chrysosporium; Daphnia magna; Chemical oxygen demand; Total organic carbon; Mortality